Inhibited Methanogenesis in the Rumen of Cattle: Microbial Metabolism in Response to Supplemental 3-Nitrooxypropanol and Nitrate - van Lingen, Henk J.; Fadel, James G.; Yáñez-Ruiz, David R.; Kindermann, Maik; Kebreab, Ermias (Frontiers in Microbiology, 2021)
3-Nitrooxypropanol (3-NOP) supplementation to cattle diets mitigates enteric CH4 emissions and may also be economically beneficial at farm level. However, the wider rumen metabolic response to methanogenic inhibition by 3-NOP and the NO-2 intermediary metabolite requires further exploration. Furthermore, NO-3 supplementation potently decreases CH4 emissions from cattle. The reduction of NO-3 utilizes H2 and yields NO-2, the latter of which may also inhibit methanogenesis, although a different mode of action than for 3-NOP and its NO-2 derivative was hypothesized. Our objective was to explore potential responses of the fermentative and methanogenic metabolism in the rumen to 3-NOP, NO-3 and their metabolic derivatives using a dynamic mechanistic modeling approach. An extant mechanistic rumen fermentation model with state variables for carbohydrate substrates, bacteria and protozoa, gaseous and dissolved fermentation products and methanogens was extended with a state variable of either 3-NOP or NO-3. Both new models were further extended with a NO-2 state variable, with NO-2 exerting methanogenic inhibition, although the modes of action of 3-NOP-derived and NO-3-derived NO-2 are different. Feed composition and intake rate (twice daily feeding regime), and supplement inclusion were used as model inputs. Model parameters were estimated to experimental data collected from the literature. The extended 3-NOP and NO-3 models both predicted a marked peak in H2 emission shortly after feeding, the magnitude of which increased with higher doses of supplement inclusion. The H2 emission rate appeared positively related to decreased acetate proportions and increased propionate and butyrate proportions. A decreased CH4 emission rate was associated with 3-NOP and NO-3 supplementation. Omission of the NO-2 state variable from the 3-NOP model did not change the overall dynamics of H2 and CH4 emission and other metabolites. However, omitting the NO-2 state variable from the NO-3 model did substantially change the dynamics of H2 and CH4 emissions indicated by a decrease in both H2 and CH4 emission after feeding. Simulations do not point to a strong relationship between methanogenic inhibition and the rate of NO-3 and NO-2 formation upon 3-NOP supplementation, whereas the metabolic response to NO-3 supplementation may largely depend on methanogenic inhibition by NO-2.